A comparison of Er,Cr:YSGG laser to minimally invasive surgical technique in the treatment of intrabony defects: Twelve‐month results of a multicenter, randomized, controlled study - Clem, Donald; Heard, Rick; McGuire, Michael; Scheyer, E. Todd; Richardson, Chris; Toback, Gregory; Gunsolley, John C.; Geurs, Nico (Journal of periodontology (1970), 2024)
Background The purpose of this publication is to report on the 12‐month clinical and radiographic results comparing the surgical use of the Er,Cr:YSGG laser (ERL) and minimally invasive surgical technique (MIST) for the treatment of intrabony defects in subjects with generalized periodontitis stage III, grade B. Methods Fifty‐three adult subjects (29 females and 24 males; 19–73 years) with 79 intrabony defects were randomized following scaling and root planing (SRP) to receive ERL monotherapy (n = 27) or MIST (n = 26). Fifty subjects completed the study. Recession (REC), probing depth (PD), clinical attachment level (CAL), treatment time, and standardized radiographs were assessed and compared for each treatment group. Clinical measurements were recorded at baseline, 4–6 weeks following SRP, and 6 and 12 months following surgical therapy. Radiographic results were compared to baseline at 6 and 12 months following surgical therapy. Results The following primary and secondary outcome variables were non‐inferior with the following margins: CAL with a non‐inferiority margin of 0.7 mm (p = 0.05), PD with a non‐inferiority margin of 0.7 mm (p = 0.05), and REC with a non‐inferiority margin of 0.4 mm (p = 0.05). Standardized radiographs suggest similar bone fill of 1.14 ± 1.73 mm for MIST and 1.12 ± 1.52 mm for ERL. Conclusions This is the first multicenter, randomized, masked, and controlled study demonstrating the ERL is not inferior to MIST at 12 months in terms of clinical outcomes and similar to MIST in terms of radiographic bone fill for the surgical treatment of intrabony defects.